2016
DOI: 10.1007/s00402-015-2387-3
|View full text |Cite
|
Sign up to set email alerts
|

Can graft choice affect return to sport following revision anterior cruciate ligament reconstruction surgery?

Abstract: The use of contralateral hamstring tendon autografts for ACL revision surgery produced similar subjective and objective outcomes at 5.2 years follow-up compared to revision with allograft patellar or Achilles tendon. Patients undergoing revision surgery with autografts experienced a quicker return to sports compared to patients who underwent allograft revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 13 publications
0
34
2
1
Order By: Relevance
“…The definition of return to sport used in each study is presented in table 2. Only three studies reported the average length of time after surgery at which patients returned to sport 19 21 26. One study found no significant difference in the mean (SD) length of time at which high school athletes (6.4 (2.8)), college athletes (7.1 (2.6) months) and recreational athletes (6.6 (2.8) months) returned to competitive sport, all of whom received a BPTB autograft 19.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The definition of return to sport used in each study is presented in table 2. Only three studies reported the average length of time after surgery at which patients returned to sport 19 21 26. One study found no significant difference in the mean (SD) length of time at which high school athletes (6.4 (2.8)), college athletes (7.1 (2.6) months) and recreational athletes (6.6 (2.8) months) returned to competitive sport, all of whom received a BPTB autograft 19.…”
Section: Resultsmentioning
confidence: 99%
“…In only one of the included studies, the primary purpose was to compare return to sport outcomes regarding the use of different graft types retrospectively 26. Two other surgical centres reported return to sport outcomes from the use of different graft types in studies using a cohort study design 22 29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autografts constitute a popular choice, 20,21 although postoperative anterior knee pain following bonepatellar tendon-bone harvesting may result in substantial impairment for patients. 22 To minimize, reduce donor-site morbidity, operative time, and incisions, allografts have been gaining in popularity 23,24 ; however, they carry the risks of immune response, disease transmission risk, delayed graft incorporation, reduced availability, and costs which may discourage their use. 25 For these reasons, we chose autologous hamstrings to perform ACL reconstruction in combination with UKR.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller cohort study of 44 patients demonstrated no major differences between allograft and autograft but showed quicker return to sports for autograft. 6 …”
Section: Discussionmentioning
confidence: 99%